Media Innovation: Technology-Based Infinity Folding Paper on Cell Splitting Materials - Salahuddin Salahuddin; Edi Rozal; Nurhaliza Nurhaliza (CV. Generasi Intelektual Digital (GEN ID), 2024)
. Innovation in technology-based learning media is increasingly needed to support an interactive and effective learning process in the digital era. However, in Indonesia, the application of innovative media such as technology-based Infinity Folding Paper is still not common. This media offers a creative and interactive alternative approach to facilitate students' independent learning. This research aims to examine the potential and development of Infinity Folding Paper learning media innovations that are integrated with digital technology. The method used is literature review with data sources from Google Scholar. The results of the study show that this media can help overcome the problem of learning effectiveness, especially in cell division material, through the presentation of visual, interactive, and flexible content. In addition, this innovation is designed to support students in understanding cell division concepts such as mitosis and meiosis independently and deeply. The findings of this research are expected to be the basis for developing technology-based learning media that are relevant, interesting, and in accordance with the needs of 21st century learning.